P20 Clinical simulation as a teaching methodology for development of new advanced clinical practitioner role at northern lincolnshire and goole NHS trust(NLaG). (3rd November 2019) - Quayle, Alexandra; Harrison, Nick; McGuffie, Rochelle
Abstract : Background: The changing face of the NHS workforce includes the new role of Advanced Clinical Practitioner (ACP), developed for experienced healthcare practitioners, characterised by a high level of skill, autonomy and complex decision making. 1 ACPs possess core and area- specific competence and training is supported by a Masters level award. Northern Lincolnshire and Goole NHS trust is developing 10 ACPs to complement the multidisciplinary clinical workforce whilst tackling recruitment and clinical gaps. In 2017 HEE produced a formal framework, identifying core capabilities and standards for ACPs, promoting four pillars underpinning practice, namely Clinical practice, Leadership and Management, Education, Research. 2 The Development Simulation Hub (DaSH) has developed a bespoke education programme for ACPs, incorporating clinical skills and simulation to consolidate existing knowledge. Method: Current ACPs were surveyed to identify clinical simulation and skills required to support their educational development. 10 ACPs, from acute care areas received 2 days of educational development, tailored carefully to their clinical areas and needs. Effectiveness of training was evaluated via a locally produced scoring system analysing both technical and non-technical areas of clinical practice post course. Multifaceted training included didactic lectures, clinical skills workshops and clinically enacted scenarios. Topics covered included: Medical Emergencies – heart failure, stroke, respiratory arrest. Surgical emergencies – massive haemorrhage, varices. Critical Care Emergencies – endotracheal intubation, pharmacology, sepsis Didactic lectures– providing up to date information and guidelines Clinical Skills– Insertion of chest drain, central venous lines, lumbar puncture Results: All ACPs (100%) scored this learning strategy as a highly effective adjunct, supporting their clinical development in addition to addressing team leadership and effective handovers. Quotations included: Very useful session, lots of knowledge gained. I will be sensible to decide when to use chest drain. Very useful session will make me more confident with identifying land marks and kits. Highlighted need for more competence and confidence with ECG. Ensure good communication. I need to be careful not to fix on a differential and remain open–minded. To keep up to date with guidelines and assess more patients in ED. Also keep attending simulation days Recommendation: Impact on Patient Care Development of clinical competence and having the ability to work collaboratively, the ACP will provide the patient with another tier of clinical care contributing to a more proficient and timely healthcare service and a positive impact on a patient's journey. References: NHS England (2017) Multi-professional framework for advanced clinical practice in England. https://www.england.nhs.uk 2. Health Education England (2017) New Framework launched to define the role of Advanced Clinical Practitioners in healthcare. https://www.hee.nhs.uk/